The Implementasi Kurikulum Merdeka di SMP Muhammadiyah 3 Depok - Vivi Anita; Wiji Hidayati; Yudiva Fya Maharani Siregar; Faisal Afandi (IAIN Parepare, 2024)
This research examines the implementation of the Independent Curriculum management initiated by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia. The Independent Curriculum aims to provide flexibility for schools and teachers in developing a curriculum that suits students' needs and potential. This study uses a qualitative approach with case study methods in several schools in various regions in Indonesia. Data was collected through in-depth interviews with school principals, teachers and educational observers, as well as analysis of curriculum documents and implementation reports. The research results show that Independent Curriculum management provides greater freedom for teachers in developing innovative teaching materials and learning methods. However, there are significant challenges in implementation, including a lack of training and assistance for teachers, limited resources, and differences in understanding of curriculum concepts at the school level. This research suggests the need to increase teacher capacity through continuous training, provision of adequate resources, and development of a comprehensive evaluation system to ensure the quality of learning in accordance with the objectives of the Independent Curriculum.